MODEL FINANCIAL QUOTIENT YANG DITERAPKAN PADA PENGHASILAN BURUH PT. MASPION SURABAYA - Sujoko, * (Program Doktor Ilmu Ekonomi, 2009)
Global crisis that happened between 2008 - 2009 year affecting at real sector and unemployment ( PHK). Affect to real sector can be seen from two aspect that is downhill of it order of client so that many company of difficulty to market its product which finally have to doefficiency for last living on of increase inflation and also difficulty of working capital so that result industry in real sector become to depress, if the situation long draw out hence will weaken company endurance and will induce at possibility to do PHK employees for the shake of lessening company burden. Condition of crisis like this is very difficult to look for work added again requirement of life which more and more high hence will emerge an expectation to free from the problem of finance. So that the key is brooding of someone in arranging finance to a period to now and future. Result of done research at labour of PT. Maspion Surabaya can be explained that most labour can be told is not smart financial because most responden still get subsidy of old fellow and owe to fulfill requirement of his life. Keyword : Financial Quotient, Earnings, Expenditure.